Mediação e conciliação: um estudo comparativo em busca de uma jurisdição sensível - Dias, Rodrigo Rodrigues (Universidade do Vale do Rio dos Sinos, 2023)
The thesis is dedicated to the evaluation of judicial mediation in the Brazilian legal system, from the perspective of users of the justice system. In effect, the investigation had, as its general objective, the study of the differences in users' experiences of justice in conciliations - within the scope of the heterocompositive process - and mediation - as an autonomous self-compositive procedure, even as a phase of the heterocompositive process -, in the perspective of analyzing whether these methods allow access to a jurisgenetic space that leads to the maximum reduction of jurispathic action. To this end, we started with the following question: does the insertion of mediation, as a new means of composing conflicts, within the scope of Positive Law, enable a process with greater democratic legitimacy, generating a jurisdiction sensitive to the normative worlds of the social agents involved? Democratic legitimacy, in this thesis, was conceived as people's subjective and rational adherence to the normativity resulting from the acts of the Judiciary, which demands greater inclusivity from subjects, who must have their pretensions, opinions and emotions integrated and considered in the process, when a decision is made. The hypothesis, based on reference literature, was based on the indication that mediation makes the process more democratic, precisely because it is based on the idea of producing legal meaning, not as an exclusivity of the State, but through the expansion of this process (democratic) based on effective access to all individuals involved, as there is an understanding that they are direct participants in the construction of decision-making acts. The field research focused on the CEJUSC (Judicial Center for Conflict Resolution and Citizenship) of the District of Toledo-PR (regarding mediation), in comparison with the Family and Succession Court of the same District (regarding conciliation) Based on a review of the doctrine, analysis of reference legislation and semi-structured interviews with users, it was found that mediation had better performance in scoring in the Likert table and, based on the qualitative analysis of the interviews, its dialogical procedure was praised, corroborating the hypothesis. However, the greatest preference on the part of those interviewed fell on traditional conciliation, with its aura of adjudication, to highlight its importance to subjects, in a culture in which participation in the Judiciary is still incipient. Therefore, even though the law – especially the New Code of Civil Procedure and the Mediation Law – are important instruments for changing culture, by themselves, they do not have the power to do so. Therefore, the thesis advocates that art. 334 of the Code of Civil Procedure, instead of encouraging self-compositional practices, ends up determining the indiscriminate sending of processes using methods little known to the parties, who are present more out of fear of the procedural sanction of the fine, than with the belief that their conflicts will be better resolved there, with full knowledge of what will be required of them to do so. Furthermore, it is noticeable that the Courts have not made the necessary investment to give CEJUSCs the dignity of judicial unity, which could provide the necessary means for the constitution of a paradigm of the culture of pacification.

La tesi è dedicata a valutare l’introduzione della mediazione giudiziaria nell’ordinamento giuridico nazionale, dal punto di vista degli utenti del sistema giudiziario. L'indagine, infatti, ha avuto come obiettivo generale quello di studiare le differenze nell'esperienza della giustizia da parte degli utenti nelle conciliazioni - nell'ambito del processo eterocompositivo - e nella mediazione - come procedura autocompositiva autonoma, anche come fase del processo eterocompositivo. -, nella prospettiva di analizzare se tali metodi consentano l'accesso ad uno spazio giurisgenetico che conduca alla massima riduzione dell'azione giurispatica A tal fine, siamo partiti dalla seguente domanda: l’inserimento della mediazione, come nuovo mezzo di composizione dei conflitti, nell’ambito del diritto positivo, consente un processo con maggiore legittimità democratica, generando una giurisdizione sensibile ai mondi normativi degli agenti sociali coinvolti? La legittimità democratica, in questa tesi, è stata concepita come l'adesione soggettiva e razionale delle persone alla normatività risultante dagli atti della magistratura, che richiede una maggiore inclusività da parte dei soggetti, i quali devono vedere le loro pretese, opinioni ed emozioni integrate e considerate nel processo, quando della consegna di una decisione. L’ipotesi, basata sulla letteratura di riferimento, si fondava sull’indicazione che la mediazione rende il processo più democratico, proprio perché si basa sull’idea di produrre significato giuridico, non come esclusività dello Stato, ma attraverso l’espansione di questo processo (democratico) basato sull’effettivo accesso a tutti gli individui coinvolti, poiché vi è la consapevolezza che essi sono partecipanti diretti nella costruzione degli atti decisionali. La ricerca sul campo si è concentrata sul CEJUSC (Centro Giudiziario per la Risoluzione dei Conflitti e la Cittadinanza) del Distretto di Toledo-PR (per quanto riguarda la mediazione), in confronto con il Tribunale di Famiglia e Successione dello stesso Distretto (per quanto riguarda la conciliazione). Dalla revisione della dottrina, dall’analisi della normativa di riferimento e dalle interviste semistrutturate agli utenti, è emerso che la mediazione ha avuto migliori performance nel punteggio nella tabella Likert e, in base all’analisi qualitativa delle interviste, è stata elogiata la sua procedura dialogica, corroborando l'ipotesi.Tuttavia, la preferenza maggiore da parte degli intervistati è caduta sulla conciliazione tradizionale, con la sua aura di aggiudicazione, per evidenziarne l'importanza per i soggetti, in una cultura in cui la partecipazione alla magistratura è ancora in fase nascente. Pertanto, anche se la legge – in particolare il Nuovo Codice di Procedura Civile e la Legge sulla Mediazione – sono strumenti importanti per cambiare la cultura, da sole non hanno il potere di farlo. Si sostiene quindi la tesi secondo cui l'art. 334 Codice de Procedura Civile., invece di incoraggiare pratiche autocompositive, finisce per determinare l'invio indiscriminato di processi con modalità poco conosciute dalle parti, le quali sono presenti più per timore della sanzione procedurale della sanzione pecuniaria che con la convinzione che lì i loro conflitti verranno risolti meglio, con piena consapevolezza di ciò che sarà loro richiesto per farlo. Inoltre, è evidente che i Tribunali non hanno fatto gli investimenti necessari per dare alle CEJUSC la dignità dell’unità giudiziaria, che potrebbe fornire i mezzi necessari per la costituzione di un paradigma della cultura della pacificazione.
Keywords: Mediação; Conciliação; CEJUSC; Conflitos; Jurisdição sensíve; Mediation; Conciliation; Conflicts; Sensitive jurisdiction; Mediazione; Conflitti; Giurisdizione sensibile; ACCNPQ::Ciências Sociais Aplicadas::Direito